Cover Image. Issue 6 (14th May 2018) - Fields, D M; Skiftesvik, A B; Browman, H I
Abstract : The cover image, by D M Fields et al., is based on the Special Issue Article Behavioural responses of infective‐stage copepodids of the salmon louse (Lepeophtheirus salmonis, Copepoda:Caligidae) to host‐related sensory cues, DOI:10.1111/jfd.12690 .